Relationship Between Sleep–Wake Disturbance and Risk of Malnutrition in Hospitalized Patients With Cirrhosis - Hui, Yangyang; Wang, Xiaoyu; Yu, Zihan; Feng, Hongjuan; Li, Chaoqun; Mao, Lihong; Fan, Xiaofei; Lin, Lin; Cui, Binxin; Chen, Xin; Sun, Longhao; Wang, Bangmao; et al. (Frontiers in Nutrition, 2021)
Both sleep-wake disturbance and malnutrition are common in cirrhosis and might be associated with similarly adverse outcomes, such as impaired health-related quality of life, hepatic encephalopathy and sarcopenia, but there is no study investigating the relationship between these 2. We aimed to explore relationship between sleep-wake disturbance (estimated by Pittsburgh Sleep Quality Index, PSQI) and malnutrition risk (estimated by Royal Free Hospital-Nutritional Prioritizing Tool [RFH-NPT]). One hundred and fifty cirrhotics were prospectively recruited. The nutritional risk is classified as low (0 points), moderate (1 point), or high (2-7 points) according to RFH-NPT score. A global PSQI > 5 indicated poor sleepers. Furthermore, multivariate linear regression analyses were performed to determine relationship between sleep-wake disturbance and malnutrition. The median PSQI was 7 and RFH-NPT was 2 in the entire cohort, with 60.67% and 56.67% rated as poor sleep quality and high malnutrition risk, respectively. Cirrhotics with poor sleep quality had significantly higher RFH-NPT score (3 vs 1, P = 0.007). Our multivariate analyses indicated that male (β= 0.279, P < 0.001), ascites (β= 0.210, P < 0.001) and PSQI (β= 0.262, P = 0.001) were independent predictors of malnutrition. In addition, the differences regarding PSQI were more significant in male, as well as those less than 65 years or with CTP-A/B or MELD <15. Taken together, sleep-wake disturbance is strongly correlated with high malnutrition risk in patients with cirrhosis. Given sleep-wake disturbance is remediable, it is tempting to incorporate therapies to reverse poor sleep quality for improving nutritional status in cirrhotics.